Quaternary deep-sea ostracode taxonomy of Ocean Drilling Program Site 980, eastern North Atlantic Ocean. (July 2014) - Yasuhara, Moriaki; Okahashi, Hisayo
Abstract : Ocean Drilling Program (ODP) Holes 980 B and C, Feni Drift at the eastern slope of the Rockall Plateau, eastern North Atlantic, were examined for late Quaternary deep-sea ostracode taxonomy. Nineteen genera and 32 species were examined and (re-)illustrated with high-resolution scanning electron microscopy images. One new species Cytheropteron paramassoni n. sp. is described and one new name Eucytherura zehali is proposed for Eucytherura hazeli Yasuhara et al., 2009. This study provides updated taxonomic information for deep-sea ostracode genera and species from the eastern North Atlantic, which is an important baseline for application of deep-sea ostracodes to paleoceanographical reconstructions and paleoecological studies in this region.